Making Remittances Work : Balancing Financial Integrity and Inclusion - Todoroki, Emiko; Noor, Wameek; Celik, Kuntay; Kulathunga, Anoma (Washington, DC: World Bank, 2014)
The September 11, 2001, terrorist attacks on the United States exposed the use of remittance channels for financing terrorism. Acting on this, the international community, through the financial action task force (FATF), issued first international standard to require the licensing or registration of money transfer businesses (MTBs) and to make them subject to anti-money laundering and combating the financing of terrorism (AML and CFT) requirements. This study aims to assess current practices, draw lessons learned, and assist policy makers in designing an effective regulatory and supervisory framework governing remittances that not only meets AML and CFT international standards, but also supports a country's overall financial inclusion objectives. The study's assessments and recommendations are based on extensive research and analysis, including primary survey data received from 26 remittance sending and receiving countries. The report follows on the 15 bilateral remittance corridor analyses (BRCAs) undertaken during 2004-10 by the financial market integrity (FMI) unit of the World Bank and three BRCAs undertaken by the Government of the Netherlands using the methodology developed by the FMI unit of the World Bank. The study is organized as follows: chapter one analyzes the various business models for remittance services currently in existence, and the various types of agent networks of MTBs available for the distribution of remittances. Chapter two elaborates on AML and CFT risks related to products, market structure, regulation, and supervision; discusses how innovative products and services for remittance transfers such as mobile money and internet-based money transfer may pose new threats and risks; and includes a discussion on the appropriate risk mitigation techniques so as not to constrain the remittance market from developing and innovating. Chapter three describes the various regulatory frameworks that MTBs encounter around the world, including different types of laws and regulations affecting them, sheds light on how AML and CFT requirements can be implemented, and provides a comprehensive analysis of customer due diligence (CDD) requirements as a crucial element to effectively fight money laundering and the financing of terrorism. Chapter four discusses licensing and registration regimes for, and appropriate regulatory approaches toward, MTBs; examines the conditions that must be fulfilled in order to apply for licensing or registration. Chapter five discusses the various AML and CFT supervisory models and identifies potential strengths and weaknesses in each of these models; elaborates on the supervisory practices of competent authorities, along with the challenges faced by MTBs in implementing relevant supervisory requirements; and discusses the risk-based approach (RBA) to supervision of MTBs. Finally, chapter six focuses on establishing an effective AML and CFT regime while supporting broader financial inclusion and highlights key policy recommendations underlined by a RBA that encourages flexible implementation of the AML and CFT framework.